THE EFFECT OF APPLYING THE PROBLEM-BASED LEARNING MODEL IN THE SUBJECT OF PRACTICAL ACCOUNTING FOR SERVICE, TRADE AND MANUFACTURING COMPANIES ON THE COMPETENCY SKILLS OF CLASS XI AKL UPT SMKN 1 SIDRAP - Dwi Dian Pratiwi; Hariany Idris; Fajriani Azis; Sitti Hajerah Hasyim; Abdul Rijal (JURNAL EDUSCIENCE, 2023)
This study aims to determine the effect of applying the problem-based learning model to the competency skills of class XI AKL UPT SMKN 1 Sidrap students. The sample in this study was taken from a total of 96 students in class XI AKL UPT SMKN 1 Sidrap. The data analysis technique used is an instrument test and hypothesis testing using SPSS 25. The instrument test consists of a validity test and a reliability test. While the hypothesis test consists of simple linear regression analysis, t test, and the coefficient of determination, pearson product moment correlation analysis. From the research results, the simple linear regression equation model Y' = 59.035 + 0.505X means that for each additional value of the problem-based learning model, the skill competency value of class students increases by 0.505 units. The results of the t-test analysis obtained 0.000 <0.05, which means that the problem-based learning model has a significant effect on students' competency skills. The results of the analysis of the coefficient of determination obtained the value of r2 = 58.1%, which means that the problem-based learning model has a contribution to the student's competency skills of 58.1. The results of the product moment correlation analysis obtained a Pearson correlation value of 0.762 and a positive value in the strong relationship between the problem-based learning model and students' competency skills.Keywords: problem based learning; student expertise competencyAbstrak Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran problem based learning terhadap kompetensi keahlian siswa kelas XI AKL UPT SMKN 1 Sidrap. Sampel dalam penelitian ini diambil dari jumlah total siswa kelas XI AKL UPT SMKN 1 Sidrap sebanyak 96 siswa. Teknik analisis data yang digunakan adalah uji instrumen dan uji hipotesis dengan menggunakan SPSS 25. Uji instrumen terdiri dari uji validitas dan uji reliabilitas. Sementara uji hipotesis terdiri dari analisis regresi linear sederhana, uji t, dan koefisien determinasi, analisis korelasi pearson product moment. Dari hasil penelitian diperoleh model persamaan regresi linear sederhana Y’=59,035+0,505X yang berarti tiap penambahan satu nilai model problem based learning, maka nilai kompetensi keahlian siswa kelas bertambah 0,505 satuan. Hasil analisis uji-t diperoleh 0,000<0,05 yang berarti model pembelajaran problem based learning berpengaruh signifikan terhadap kompetensi keahlian siswa. Hasil analisis koefisien determinasi diperoleh nilai r2 = 58,1% yang berarti model pembelajaran problem based learning memiliki kontribusi terhadap kompetensi keahlian siswa sebesar 58,1. Hasil analisis korelasi product moment diperoleh nilai pearson corelation sebesar 0,762 dan bernilai positif berada pada hubungan kuat antara model pembelajaran problem based learning dan kompetensi keahlian siswa.Kata Kunci: problem based learning; kompetensi keahlian siswa